Investigation of Heavy Metal Accumulation in Vegetables and Health Risk to Humans From Their Consumption - Gupta, Neha; Yadav, Krishna Kumar; Kumar, Vinit; Prasad, Shiv; Cabral-Pinto, Marina M. S.; Jeon, Byong-Hun; Kumar, Sandeep; Abdellattif, Magda H.; Alsukaibia, Abdulmohsen Khalaf Dhahi (Frontiers in Environmental Science, 2022)
Heavy metals contamination of soil and edible parts of vegetables is presently a challenging environmental issue worldwide. The present study determined the accumulated amount of cadmium (Cd), lead (Pb), nickel (Ni), cobalt (Co), zinc (Zn), copper (Cu), and manganese (Mn) in soil, coriander, onion, and tomato collected from agricultural fields of Jhansi city, India. The bio-concentration factor and non-carcinogenic health risks were also assessed to know the vegetables’ accumulation potential of heavy metals from soil and possibility to have non-carcinogenic health risks via an intake of these vegetables. The samples were digested using di-acid solution prior to heavy metals analysis by atomic absorption spectrometric method. The average content of Cd, Pb, Ni, Co, Zn, Cu, and Mn were 2.02, 19.09, 21.56, 9.31, 35.34, 14.96, and 15.21 mg/kg dry weight (dw) in soil, 0.23, 2.12, 0.77, 0.47, 36.65, 5.92, and 21.65 mg/kg dw in coriander, 0.13, 0.66, 0.54, 0.32, 23.94, 6.25, and 20.15 mg/kg dw in onion, 0.14, 0.46, 0.89, 0.22, 16.77, 4.77, and 14.46 mg/kg dw in tomato, respectively. The bio-concentration factor revealed significant accumulation of Zn (1.04) and Mn in coriander (1.42), and in onion (1.32). The target hazard quotient and health risk index signaled that the population consuming these vegetables is risk-free. However, it is recommended that the concentration of heavy metals in the soil and crops of the study area and its related health risks be regularly monitored to avoid significant health risks in the future.